Comparative Analysis of The Benefits of Sukuk and Bonds in Indonesia - Mardiyah, Suci; Zahrah, Alfiatun; Syaipudin, Muhammad; Hasda, Mifta; Sudirman, Wahyu Febri Ramadhan (Journal of Financial and Business, 2024)
This research aims to analyze the comparison of profits between sukuk and bonds in Indonesia, focusing on aspects such as structure, principles, and regulations, as well as the risk and profit profile of each instrument. Sukuk, which is based on Islamic sharia principles, offers the benefits of real asset ownership and profit-sharing-based income, while conventional bonds offer certainty of income through fixed interest payments. This study also discusses regulations governing the issuance of sukuk and bonds, and their impact on investment security and transparency. The analysis results show that sukuk are more attractive to investors who seek sharia compliance and stability in real assets, while bonds are more attractive to those who want income certainty and investment flexibility. This research concludes that the choice between sukuk and bonds must be adjusted to the risk profile, investment objectives, and personal preferences of each investor in Indonesia.